Case report: further delineation of AEBP1-related Ehlers–Danlos Syndrome (classical-like EDS type 2) in an additional patient and comprehensive clinical and molecular review of the literature - Yamaguchi, Tomomi; Hayashi, Shujiro; Nagai, So; Uchiyama, Akihiko; Motegi, Sei-Ichiro; Fujikawa, Tomomi; Takiguchi, Yuri; Kosho, Tomoki (Frontiers in Genetics, 2023)
The Ehlers–Danlos Syndromes (EDS), a group of hereditary connective tissue disorders, were classified into 13 subtypes in the 2017 International Classification. Recently, a new subtype of EDS called classical-like EDS type 2 (clEDS2), which is caused by biallelic variants in the adipocyte enhancer binding protein 1 (AEBP1) gene, was identified. We describe the 11th patient (9th family) with clEDS2, who was complicated by a critical vascular event (superior mesenteric artery aneurysm and rupture). A next-generation sequencing panel-based analysis revealed compound heterozygous variants in AEBP1: NM_001129.5:c.[2296G>T]; [2383dup], p.[(Glu766*)]; [(Glu795Glyfs*3)]. Light microscopic analyses showed increased interfibrillar spaces in the reticular dermis, a disorganized arrangement of collagen fibers, and decreased collagen content. An electron microscopic analysis showed the presence of collagen fibrils with irregular contours (flower-like appearance) and small collagen fibrils. A biochemical analysis showed reduced secretion of type I and type III procollagen. Clinical and molecular features of the current patient and all previously reported patients were reviewed comprehensively. Manifestations noted in most cases (>80%) included skin features (hyperextensibility, atrophic scars, easy bruising, excessive skin/skin folding, delayed wound healing, translucency, piezogenic papules), skeletal features (generalized joint hypermobility, dislocations/subluxations, pes planus), dental abnormalities, and neuromuscular abnormalities. Critical complications, each occurring in a single case, included superior mesenteric artery multiple aneurysm and rupture, aortic root dilation requiring surgery, and bowel rupture. Most AEBP1 variants were predicted or experimentally confirmed to lead to nonsense-mediated mRNA decay, whereas one variant resulted in a protein that was retained intracellularly and not secreted. Clinical, molecular, pathological, and biochemical features of the current patient, as well as a review of all previously reported patients, suggest the importance of the aortic carboxypeptidase-like protein encoded by AEBP1 in collagen fibrillogenesis.